2013
DOI: 10.1557/jmr.2013.72
|View full text |Cite
|
Sign up to set email alerts
|

Defects in amorphous phase-change materials

Abstract: Understanding the physical origin of threshold switching and resistance drift phenomena is necessary for making a breakthrough in the performance of low-cost nanoscale technologies related to nonvolatile phase-change memories. Even though both phenomena of threshold switching and resistance drift are often attributed to localized states in the band gap, the distribution of defect states in amorphous phase-change materials (PCMs) has not received so far, the level of attention that it merits. This work presents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 40 publications
(50 reference statements)
8
32
1
Order By: Relevance
“…Our measurements of thick films enable the determination of the absorption coefficient over a large energy range. They confirm that, on aging, the band gap indeed increases, consistent with previous PDS 44 and ellipsometry data 43 . In addition, the PDS data in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Our measurements of thick films enable the determination of the absorption coefficient over a large energy range. They confirm that, on aging, the band gap indeed increases, consistent with previous PDS 44 and ellipsometry data 43 . In addition, the PDS data in Fig.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, it has been shown that after accelerated drift by annealing, the band gap is increased, 12,24 while the shape of the temperature dependence is preserved. 25 In particular for GeTe, an increase of the band gap upon annealing at 413 K by about 9% has been measured. 25 Based on these findings, the temperature dependent resistance shown in Fig.…”
Section: Discussionmentioning
confidence: 98%
“…25 In particular for GeTe, an increase of the band gap upon annealing at 413 K by about 9% has been measured. 25 Based on these findings, the temperature dependent resistance shown in Fig. 3(a) has been modeled using Eqs.…”
Section: Discussionmentioning
confidence: 98%
“…The drift and the noise behavior have both been attributed to the large defect distributions within the amorphous phase that dominate the transport behavior [11][12][13][14][15][16]. In this study, we establish a link between the changes in the electrical resistance upon drift and changes in the electronic density of states (DoS).…”
Section: Introductionmentioning
confidence: 88%